Effect of LaB6 content on the gas evolution and structure of ZrC coating for carbon/carbon composites during ablation. Issue 4 (March 2017) - Jia, Yujun; Li, Hejun; Yao, Xiyuan; Zhao, Zhigang; Sun, Jiajia
Abstract: ZrC coatings with different contents of LaB6 for SiC-coated carbon/carbon composites were fabricated by supersonic atmosphere plasma spraying. The mechanism of gas evolution during oxidation at ultra-high temperatures and the oxide scale structure evolution of the coating after addition of LaB6 with different contents were studied. Results showed that rare earth borate rather than rare earth oxide mainly reduced the melting resistance of the oxide scale. The oxide scale for ZrC coating with 10% LaB6 was unfavorable to the gas escape. After addition of 20% LaB6, the oxide scale was favorable to the gas escape but disadvantageous to the coating applied in the environment containing scouring because of the reduced melting resistance. High content of LaB6 also could cause evident boiling of B2 O3, leading to producing big pores in the oxide scale during ablation. Appropriate content of LaB6 for ZrC coating was found to be 15%.